Intellectual capital and its impact on market value and financial performance - an applied study of a sample of banks listed on the Iraqi Stock Exchange for the period from (2008-2013) - Hind Dia Abdel Rasoul (Iraqi Journal for Administrative Sciences, 2025)
The idea of the research focuses on the nature and type of relationship that links intellectual capital to the dimensions of market value and financial performance among a sample of 20 banks for the period from 2008-2013. The researcher decided to build four mathematical models through the multiple regression equation, and to test the relationships between the variables, a number of statistical methods were used. Suitability such as linear relationship, equality of variance, and (D-W) test. As for testing the hypotheses, Pearson analysis and linear regression analysis were used. The research has reached a number of conclusions, the most prominent of which is that banks’ possession of intellectual capital as an asset contributes to achieving competitive advantage and indicates a positive and morally significant correlation and influence between intellectual capital and both the market value and financial performance of the banks in the research sample. Finally, the research recommended the need to benefit from Intellectual capital measures to diagnose and enhance this asset in line with maximizing the bank’s value and improving its financial performance.